Altered Resting-State Brain Activities in Drug-Naïve Major Depressive Disorder Assessed by fMRI: Associations With Somatic Symptoms Defined by Yin-Yang Theory of the Traditional Chinese Medicine - Xu, Zhexue; Zhang, Shu; Huang, Liyuan; Zhu, Xiaolei; Zhao, Qing; Zeng, Yawei; Zhou, Dongfeng; Wang, Di; Kuga, Hironori; Kamiya, Atsushi; Qu, Miao (Frontiers in Psychiatry, 2018)
Identification of biological markers for defining subtypes of major depressive disorder (MDD) is critical for better understanding MDD pathophysiology and finding effective treatment intervention. The “Yin and Yang” theory is a fundamental concept of traditional Chinese Medicine (TCM). The theory differentiates MDD patients into two subtypes, Yin and Yang, based on their somatic symptoms, which had empirically been used for the delivery of effective treatment in East Asia. Nonetheless, neural processes underlying Yin and Yang types in MDD are poorly understood. In this study, we aim to provide physiological evidence using functional magnetic resonance imaging (fMRI) to identify altered resting-state brain activity associated with Yin and Yang types in drug-naïve MDD patients. The Yin type and Yang type MDD patients showed increased amplitude of low-frequency fluctuation (ALFF) in different cortical brain areas in the parietal, temporal, and frontal lobe, compared to matched healthy controls. Differential ALFF is also observed in several cortical areas in frontal lobe and insula between Yin and Yang type group. Of note, although ALFF is increased in the inferior parietal lobe in both Yin and Yang type group, inferior parietal lobe-centered functional connectivity (FC) is increased in Yang type, but is decreased in Ying type, compared with matched healthy controls. These results suggest that differential resting-state brain activity and functional connectivity in Yin and Yang types may contribute to biological measures for better stratification of heterogeneous MDD patients.